2021
DOI: 10.3390/ijms22105318
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Serves as a Balanced Agonist for MRGPRX2 and a Single Tyrosine Residue Is Required for β-Arrestin Recruitment and Receptor Internalization

Abstract: The neuropeptide substance P (SP) mediates neurogenic inflammation and pain and contributes to atopic dermatitis in mice through the activation of mast cells (MCs) via Mas-related G protein-coupled receptor (GPCR)-B2 (MrgprB2, human ortholog MRGPRX2). In addition to G proteins, certain MRGPRX2 agonists activate an additional signaling pathway that involves the recruitment of β-arrestins, which contributes to receptor internalization and desensitization (balanced agonists). We found that SP caused β-arrestin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
(99 reference statements)
1
27
0
Order By: Relevance
“…Downstream signaling of MRGPRX2, Erk1/2, is involved in the induction of PGD2 de novo synthesis in MCs by SP [ 42 ]. In addition to G-protein signaling, C48/80 or SP recruits β-arrestin 1 via MRGPRX2 to internalize and desensitize MRGPRX2 at the plasma membrane [ 54 , 55 ] and to activate the ERK signaling pathway [ 40 ]. On the other hand, another MRGPRX2 ligand, AG-30/5C or icatibant, does not internalize MRGPRX2 [ 56 ].…”
Section: Mrgprx2mentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream signaling of MRGPRX2, Erk1/2, is involved in the induction of PGD2 de novo synthesis in MCs by SP [ 42 ]. In addition to G-protein signaling, C48/80 or SP recruits β-arrestin 1 via MRGPRX2 to internalize and desensitize MRGPRX2 at the plasma membrane [ 54 , 55 ] and to activate the ERK signaling pathway [ 40 ]. On the other hand, another MRGPRX2 ligand, AG-30/5C or icatibant, does not internalize MRGPRX2 [ 56 ].…”
Section: Mrgprx2mentioning
confidence: 99%
“…The lack of functional desensitization and internalization of MRGPRX2 caused by the biased ligands may enhance immune modulation. It has been reported that the phosphorylation of Tyr279 at the cytoplasmic end of the TM7 domain is important for the induction of MRGPRX2 internalization by the balanced ligand, SP [ 55 ]. In the future, the full picture of the biological effects of the different mechanisms of MRGPRX2 activation by the balanced and biased ligands will be clarified.…”
Section: Mrgprx2mentioning
confidence: 99%
“…As a G protein-coupled receptor (GPCR), MRGPRX2 initiates signaling by activation of G proteins. Which G protein subsets are involved is not completely clear, since pertussis toxin (PTX), a G αi inhibitor [10,11]), and YM-254890, that is G αq specific [12], have been variably shown to interfere with MRGPRX2 signaling [13][14][15]; it is assumed that the cell type expressing MRGPRX2 plays a decisive role, but no data are currently available for skin MCs. However, cutaneous MCs are not only the most abundant MC population in the body [16], but they also express the highest levels of MRGPRX2 and respond most vigorously to its ligands [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…β-arrestin 2 is encoded by the human ARRB2 gene and is an intracellular adaptor/scaffold protein that is highly expressed in the central nervous system. The main function of the β-arrestin family is to negatively regulate the activation and phosphorylation of the G-protein-coupled receptor signaling pathway, which promotes agonist-mediated desensitization and internalization and leads to the inhibition of cellular responses to stimuli such as neurotransmitters, hormones, and sensory signals [ 47 ]. Studies have shown that β-arrestin 2 inhibits β-adrenergic receptor function in vitro and participates in the regulation of synaptic receptors [ 48 ].…”
Section: Discussionmentioning
confidence: 99%